Project Based Learning to Improve Student Learning Outcomes in Elementary Schools - Rahmatika, Nada; Dwi pratiwi, Dinda; Diah Saptorini, Yuli; Agnesta Putri, Lara; Salsabila, Ananda (International Journal of Elementary School, 2024)
This research aims to evaluate the effectiveness of implementing the Project-Based Learning method in improving student learning outcomes in elementary schools. Project-Based Learning is a learning approach that emphasizes active student involvement through real-world projects relevant to the subject matter. Through Project-Based Learning, students are expected to develop critical thinking skills, collaboration, and the ability to apply knowledge in everyday life contexts. This research employs the Classroom Action Research method, which consists of four stages: planning, action, observation, and reflection. The improvement in student abilities is evident from their final grades, with scores categorized as "good" (72.85) and "very good" (83.57). The student assessment results also indicate satisfactory outcomes, with a cumulative learning completion score exceeding 40% and an excellent rate of 92%. Based on these findings, students' creative thinking abilities, particularly regarding the material and their needs, show significant improvement through the application of the Project-Based Learning model.